2015
DOI: 10.11113/jt.v76.5652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Geometrical Parameters Interaction on Swirl Effervescent Atomizer Spray Angle

Abstract: A wider spray angle produced by an atomizer is often required in providing a better spray dispersion. The formation and wideness of the spray angle were reported to be affected by the changes in geometrical parameters. In the present study, the effect of the interaction between two geometrical parameters (swirl-generating vane angle and discharge orifice diameter) on the swirl effervescent atomizer spray angle was studied. A newly-designed swirl effervescent atomizer was developed with 30°, 45° and 60° swirl-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…PCR amplification was done for extracted DNA of bacteria in a perfect amount of 25 ul contented 5 ul template DNA, 0.5 ul of each of the primers, nuclease free water 6.5 ul, and master mix 12.5 ul, The PCR thermocycler program described in Table (2). PCR output were discreted on 1.5 % agarose gel with ethidium bromide and imagened beneath UV light, then photographed by digital camera.…”
Section: C-pcr Amplificationmentioning
confidence: 99%
“…PCR amplification was done for extracted DNA of bacteria in a perfect amount of 25 ul contented 5 ul template DNA, 0.5 ul of each of the primers, nuclease free water 6.5 ul, and master mix 12.5 ul, The PCR thermocycler program described in Table (2). PCR output were discreted on 1.5 % agarose gel with ethidium bromide and imagened beneath UV light, then photographed by digital camera.…”
Section: C-pcr Amplificationmentioning
confidence: 99%
“…The papers [50][51][52] described an innovative design of an effervescent-swirl atomizer equipped with various types of swirl inserts (Figure 3). Three insert channels with different inclination angles were tested (Figure 4), for which the said angle was 30, 45, and 60 • C, respectively.…”
Section: Building Construction and Designmentioning
confidence: 99%
“…Jedelsky and Jicha [6] varied the intensity of the swirl-generating vane and discovered that a more intense swirl-generating vane produces a larger spray angle. Ghaffar et al, [7] observed the combined effect of swirl-generating vane intensity and discharge orifice diameter resulting in a wide spray angle discharging from a swirl effervescent atomizer. Ghaffar et al, [8] encountered the dependency of spray angle to the injection pressure alongside the atomizer geometrical parameters.…”
Section: Introductionmentioning
confidence: 99%